FRI0486 Tocilizumab Treatment for Uveitic Cystoid Macular Edema Refractory To Other Synthetic and Biological Immunosuppressive Drugs. Multicentre Study of 23 Patients. (15th July 2016) - Beltrán-Catalán, E.; Fernandez, C.; Blanco, R.; Calvo-Río, V.; Hernandez, M.; Mesquida, M.; Adan, A.; Hernandez, V.; Diaz, D.; Diaz, G.; Calvo, I.; Atanes, A.; et al.
Abstract : Objectives: Cystoid macular edema (CME) is the leading cause of blindness in uveitis, which often requires more aggressive treatment based on associating corticosteroids and synthetic and biological systemic immunosuppressive drugs. Our objective was to evaluate the efficacy and safety of Tocilizumab (TCZ) in a series of patients with refractory CME. Methods: A Multicentre study of 23 patients with CME secondary to non-infectious uveitis who had inadequate response or intolerance to traditional treatment with corticosteroids and at least one conventional immunosuppressive drug including in some cases biological therapy. CME was defined by (OCT>300μ). The outcome variables were the degree of inflammation of the anterior chamber and vitreous, visual acuity and macular thickness. The results are expressed as mean ± SD for normally distributed variables, or as median [interquartile range] when are not. Comparison of continuous variables was performed using theWilcoxon test. Results: 23 patients (16 females/7 males) with CME were studied. With a mean age of 33.5±17.7 years. Associated disease were: juvenile idiopathic arthritis (n=9), Behçet's disease (n=6), Birdshot retinochoroidopathy (n=4) and idiopathic (n=4). Ocular pattern was: panuveitis (n=8), anterior uveitis (n=6), posterior uveitis (n=5) and intermediate uveitis (n=4). Most patients had bilateral involvement (n=22). Prior to TCZ patients received: intraocular corticosteroids (n=20), intravenous methylprednisolone (n=6), methotrexate (MTX) (n=18), cyclosporine A (CsA) (n=16), mycophenolate (n=4), azathioprine (n=2), cyclophosphamide (n=1), sulfasalazine (n=1), daclizumab (n=1), acetazolamide (n=1), thalidomide (n=1), leflunomide (N=1), infliximab (n=8), adalimumab (n=17), etanercept (n=2), golimumab (n=2), rituximab (N=2), abatacept (n=3), anakinra (n=1). TCZ administration schedule was 8 mg/kg/4 weeks iv. in all patients except in one that administration was every 2 weeks. Monotherapy (n=11) and in combination with conventional immunosuppressive: MTX (n=6), CsA (n=5) and leflunomide (n=1). A statistically significant reduction was observed in macular thickness from 418.84±177.14 to 240.00±54.73 m; p=0.00009 during the first year of treatment with TCZ. Most of intraocular inflammation parameters showed also a rapid improvement after initiation of TCZ. (TABLE) Visual acuity improved in a statistically significant way from 0.4±0.32 at baseline to 0.59±0.30 after a year of treatment p=0.0002. Prednisone dose was reduced from 15.69±14 to 2.92±2.46 after a year of treatment. After 13.1±8.55 months minor side effects were observed: nausea (n=1), viral conjunctivitis (n=1) and bullous impetigo (n=1). Remission was achieved in 13 patients. Conclusions: TCZ seems an effective and safe treatment in patients with uveitic CME refractory to other synthetic and biological immunosuppressive drugs. Disclosure of Interest: None declared